Preparation and properties of soap‐free emulsion of polyacrylate grafted by polyester with high HEMA content. Issue 9 (27th December 2022) - Zhang, Xinxin; Gong, Shuling
Abstract: A waterborne polyacrylate with high methacrylicacid‐β‐hydroxyethyl ester (HEMA) content is synthesized by copolymerization of acrylate monomers and unsaturated polyester in soap free seed semi‐continuous emulsion. The unsaturated polyester is prepared by transesterification between the polyester with high hydroxyl content and methyl methacrylate (MMA). The influences of the HEMA content, acrylic acid (AA)/ methacrylic acid (MAA), and butyl acrylate (BA)/ styrene (St) ratio on properties of the emulsion and crosslinked films are discussed. The emulsion modified by copolymerization yields a high hydroxyl value (167 mgKOH g −1 ) and a low acid value (30.5 mgKOH g −1 ). The high hydroxyl content not only provides crosslinked sites for improving properties but also facilitates further curing if it does not degrade the stability of the emulsion. The modification by compolymerization is superior to modification by blending. The emulsion is further cured with amino resin HMMM and the optimum curing ratio is 6:1 of emulsion: HMMM. The crosslinked films have a high hydrophobicity and the water absorption is only 2.46%. Meanwhile, the film has good mechanical properties with the tensile strength reaches 7.5 MPa and the Young's modulus is 97.64 MPa. Abstract : Waterborne polyacrylate emulsion with high hydroxyl value is successfully synthesized by copolymerizion modification of polyester. The modified waterborne acrylate emulsion not only overcomes the high hydrophilicity, but also provides more effective sites for preparing high performance paint films by crosslinking with amino resin. The film has certain tensile strength and excellent water and solvent resistance.